New findings on inhibitor development: from registries to clinical studies. (January 2017) - Peyvandi, F.; Ettingshausen, C. E.; Goudemand, J.; Jiménez‐Yuste, V.; Santagostino, E.; Makris, M.
Abstract : The high incidence of inhibitors against factor VIII (FVIII) concentrates in patients with haemophilia A has encouraged debate as to whether product‐type plays a role. There is debate in the literature as to whether rFVIII concentrates are associated with a higher incidence of inhibitors compared to pdFVIII products. The management of haemophilia in patients with inhibitors includes on‐demand/prophylaxis treatment with bypassing agents, and/or immune tolerance induction (ITI). However, these options create an economic and emotional burden on patients, their families and healthcare practitioners. Although ITI eliminates inhibitors successfully in 60–80% of cases, it is costly. Despite high costs, preliminary data from a decision analytical model have indicated that ITI is economically advantageous compared with on‐demand/prophylactic treatment with bypassing agents. In patients with persistent inhibitors and those who are not candidates for ITI or have failed ITI, bleeding‐related mortality and morbidity increase and quality of life decreases, compared with non‐inhibitor patients. This article provides an update on the risk of inhibitor development and discusses best management approaches for patients with high‐risk factors for inhibitor development.